Convective boiling heat transfer of methanol – Hydrogen peroxide solutions in a microchannel evaporator. (October 2019) - Chang, Ya-Ting; Tseng, Fangang; Su, Yu-Chian; Pan, Chin
Highlights: Develop a divergent microchannel evaporator with an innovative inlet design. Decomposition of hydrogen peroxide making the boiling of the mixture extraordinary. An optimal flow rate of 0.36 ml/min enhancing the critical heat flux most. The mixture with C = 1/3 demonstrates the best heat transfer coefficient. Competing effects between Marangoni convection and two-phase flow instability. Abstract: To provide uniform mixture of methanol vapor, steam and oxygen in a methanol reformer, the present study investigates the boiling heat transfer performance and two-phase flow of methanol and 50 wt% hydrogen peroxide mixture in an microchannel evaporator with V-shaped micro diffusers for the entrance region and 52 parallel diverging channels. The decomposition of hydrogen peroxide may produce oxygen and significant amount of heat making the convective boiling of the mixture extraordinary. Experiments of three volume ratios (C) of hydrogen peroxide to methanol of 1/2, 1/3, 1/4 and three flow rates, 0.18, 0.36, and 0.54 ml/min are conducted and analyzed. The experimental results reveal that the addition of hydrogen peroxide can significantly enhance boiling heat transfer as well as the critical heat flux possibly due to the Marangoni convection caused by concentration gradient, but the enhancement is limited by the introduction of decomposition heat internally in the working fluid. The oxygen and enhanced evaporation due to decomposition may make the boiling two-phase flow unstable and deteriorate the heat transfer. Consequently, the mixture with C = 1/3 showing the best heat transfer coefficient may be the optimized working fluid for a microchannel evaporator to serve the purpose of this study.